Identification of suitable media based on hydroponic culture for production Zucchini squash - Suvo, TP; Ahamed, MT; Haque, MR; Chakrobarti, M; Biswas, H (International Journal of Agricultural Research, Innovation and Technology, 2017)
An experiment was conducted to identify the hydroponic culture based suitable media for the production of Zucchini Squash in the Biochemistry Laboratory, Patuakhali Science and Technology University, Dumki, Patuakhali, Bangladesh during 2014. Zucchini plant (Cucurbita pepo L.) were grown in closed soilless systems to determine the effect of four different hydroponics media on plant growth, yield and nutrient contents (fruit moisture content, ascorbic acid content on fruit, fruit protein content, protein content in leaves). Three types of substrates (coconut husk, jute, cotton) along with Hoagland solution were used in this experiment. Result revealed that media using Jute fiber showed significant effect on plant growth and nutritional values than the other media (media of cotton with Hoagland solution, coconut husk with Hoagland solution and only Hoagland solution). The plant grown using jute media showed the highest plant height (60.33 cm), number of leaves (17.33), yield (1.5 kg plant-1), fruit moisture content (97.33%), Ascorbic acid content in fruit (28.73 mg 100g-1), protein percentage in fruit (1.406%) and percentage (1.326%) in leaves than the other media. Therefore, with the controlled nutrient supply, less expense, less labor, no use of pesticides or fertilizer with controlled environment the use of jute fiber as a substrate with Hoagland solution can be an effective one. Int. J. Agril. Res. Innov. & Tech. 6 (2): 1-4, December, 2016